Topical Dexamethasone Administration Impairs Protein Synthesis and Neuronal Regeneration in the Olfactory Epithelium - Crisafulli, Umberto; Xavier, André M.; dos Santos, Fabiana B.; Cambiaghi, Tavane D.; Chang, Seo Y.; Porcionatto, Marimélia; Castilho, Beatriz A.; Malnic, Bettina; Glezer, Isaias (Frontiers in Molecular Neuroscience, 2018)
Chronic inflammatory process in the nasal mucosa is correlated with poor smell perception. Over-activation of immune cells in the olfactory epithelium (OE) is generally associated with loss of olfactory function, and topical steroidal anti-inflammatory drugs have been largely used for treating such condition. Whether this therapeutic strategy could directly affect the regenerative process in the OE remains unclear. In this study we show that nasal topical application of Dexamethasone (DEX; 200 or 800 ng/nostril), a potent synthetic anti-inflammatory steroid, attenuates OE lesion caused by gram-negative bacteria lipopolysaccharide (LPS) intranasal infusion. In contrast, repeated DEX (400 ng/nostril) local application after lesion establishment limited the regeneration of olfactory sensory neurons (OSNs) after injury promoted by LPS or methimazole. Remarkably, DEX effects were observed when the drug was infused as three consecutive-days regimen. The anti-inflammatory drug does not induce OE progenitor cell death, however, disturbance in mTOR downstream signaling pathway and impairment of protein synthesis were observed during the course of DEX treatment. In addition, in vitro studies conducted with OE neurospheres in the absence of an inflammatory environment showed that glucocorticoid receptor (GR) engagement directly reduces OE progenitor cells proliferation. Our results suggest that DEX can interfere with the intrinsic regenerative cellular mechanisms of the OE, raising concerns on the use of topical anti-inflammatory steroids as a risk factor for progressive olfactory function impairment.